2014
DOI: 10.1016/j.toxrep.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid exposure triggers oxidative stress in the mouse pancreas

Abstract: HighlightsPFOA triggers focal ductal hyperplasia following 7 day exposure.PFOA exposure increases 8-iso-PGF2α levels in the pancreas.Antioxidant gene expression is upregulated in the pancreas following PFOA exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…In the present study, it was found that ¼ LC 50 and LC 50 PFOA (28.2 and 112.8 μM, respectively) caused apoptosis and necrosis in fetal mouse oocytes in vitro after their exposure for 24 hours to the PFC. The observed oocyte cytotoxicity of PFOA is probably related to induction of apoptosis via intracellular ROS generation, as it has been reported in other cell types . Excess ROS would lead to lipid peroxidation, protein degradation and DNA damage, which eventually would result in oocyte death …”
Section: Discussionmentioning
confidence: 59%
“…In the present study, it was found that ¼ LC 50 and LC 50 PFOA (28.2 and 112.8 μM, respectively) caused apoptosis and necrosis in fetal mouse oocytes in vitro after their exposure for 24 hours to the PFC. The observed oocyte cytotoxicity of PFOA is probably related to induction of apoptosis via intracellular ROS generation, as it has been reported in other cell types . Excess ROS would lead to lipid peroxidation, protein degradation and DNA damage, which eventually would result in oocyte death …”
Section: Discussionmentioning
confidence: 59%
“…ROS are reactive molecules or free radicals that generated as a byproduct of normal aerobic metabolism, and the production of ROS has been regarded as a possible toxicity mechanism of polluted water in aquatic organisms [29]. Under normal physiological conditions, these highly reactive substances can be continually balanced by the antioxidant defense system comprising of antioxidant enzymes like superoxide dismutase (SOD) and low-molecular-weight scavengers like reduced glutathione (GSH).…”
Section: Introductionmentioning
confidence: 99%
“…In mouse testis, the lowest dose tested of 2.5 mg/kg/day PFOA increased MDA and hydrogen peroxide levels, decreased the expression of the oxidant-sensitive transcription factor, Nrf2, and inhibited the activities of antioxidant enzymes (superoxide dismutase and catalase) [91]. PFOA also induces oxidative stress in a dose-dependent manner from 0.5 to 5 mg/kg/day in the mouse liver and pancreas [25], and a variety of tissues including rat pancreatic β-cells [92], mouse testes and epididymis [93], and mouse ovary [94]. Similarly, in vivo and in vitro studies have demonstrated that PFOS exposure results in oxidative stress, evidenced by the production of ROS, changes in antioxidant enzymes, elevation of lipid peroxidation products and changes in Nrf2 [32,[95][96][97].…”
Section: Induces Oxidative Stressmentioning
confidence: 91%
“…Unlike organochlorine aromatic compounds such as polychlorinated biphenyls, chlorinated dioxins and dichlorodiphenyltrichloroethane (DDT), PFAS are not lipophilic and do not accumulate in adipose tissue [24]. In vivo, PFAS bind to proteins in the blood such as albumin and have been detected in tissues including the liver, pancreas, kidney, lung and brain [25,26]. PFAS readily cross the placenta and are detected in cord blood and fetal tissues, as well as in breast milk [27,28].…”
Section: Existing Research On Pfas Exposure and Cancer Riskmentioning
confidence: 99%